Ecological Engineering - Ecological Engineering (Elsevier, 2026)
Ecological engineering has been defined as the design of ecosystems for the mutual benefit of humans and nature. The journal is for those involved in designing, monitoring, or restoring ecosystems, and serves as a bridge between the fields of ecology and engineering.
FI 0.75
Q1
Keywords: Agriculture; Aquaculture & Food Science; Agriculture & Ecology; Agricultura; Ecología; Acuerdos transformativos; Transformative agreements; Reconstrucción de hábitats; Ecotecnología; Ecología sintética; Bioingeniería; Ecología de la restauración; Conservación ecológica; Rehabilitación de ecosistemas; Restauración de arroyos y ríos; Conservación de recursos no renovables